(untitled) (Journal of Applied Oral Science, 2013)
Objectives: This study evaluated the influence of different exposure times to saliva in situ in comparison with an antioxidant treatment on composite resin bond strength to human enamel restored after tooth bleaching. Material and Methods: Forty human teeth specimens measuring 5x5 mm were prepared and randomly allocated into 5 groups with 8 specimens each: Gct (control group, restored on unbleached enamel); Gbl (restored immediately after bleaching); Gsa (bleached, treated with 10% sodium ascorbate gel for 60 min and restored); G7d (bleached, exposed to saliva in situ for 7 days and restored); and G14d (bleached, exposed to saliva in situ for 14 days and restored). Restored samples were cut into 0.8 mm2 sticks that were tested in microtensile. Specimens were microscopically analyzed and failure modes were classified as adhesive, cohesive, or mixed. Pretest and cohesive failures were not considered in the statistical analysis, which was performed with one-way ANOVA and Tukey's post-hoc test (α=0.05), with the dental specimen considered as the experimental unit. Results: Mean bond strength results found for Gbl in comparison with Gct indicated that bleaching significantly reduced enamel adhesiveness (P;0.05). Bond strength found for G14d was significantly higher than for Gsa (P